Design and analysis of a novel tri-band flower-shaped planar antenna for GPS and WiMAX applications. Issue 9 (13th June 2017) - Ullah, Sadiq; Faisal, Farooq; Ahmad, Ashfaq; Ali, Usman; Tahir, Farooq Ahmad; Flint, James A.
Abstract: This paper presents the design of a tri-band flower-shaped planar monopole antenna operating at three frequencies i.e. 1.576 (GPS), 2.668, and 3.636 GHz (Mobile WiMAX). The radiating element of the antenna is backed by a 1.6 mm thicker FR-4 substrate having a dielectric constant of 4.3. The substrate is backed by a truncated ground plane. The antenna is fed through a 50 Ω microstrip line. The flower shape of the radiating element is derived from the basic circular shape by introducing in it rounded slots of various radii. The upper part of the antenna is flower shaped while the lower part comprises a microstrip feed line and two branches, each having two "leaves" at the end. The leaves and branches contribute in the impedance matching of the lower (1.576 GHz) and middle (2.668 GHz) frequency bands. The antenna gives an acceptable simulated efficiency >70% in the three frequency bands. Suitable gains of 1.63, 2.59, and 3.23 dB are obtained at 1.576, 2.668, and 3.636 GHz, respectively. The antenna matched with a VSWR < 1.2 in the three frequency bands. The prototype of the antenna is fabricated and tested in the laboratory, and good agreement in simulated and measured results is achieved. The proposed design is a visually appealing and may find uses as an external antenna in GPS and WiMAX applications.